Translanguage - Al Khafaji, Adil H. A. (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis work proposes a hypothesis that could stand as a basis for empirical investigation of translation process without losing sight of translation product. The proposed hypothesis can provide guidelines to investigate three possible concerns: First, the developmental nature of translators’ transitional constructions before settling on a “final” version. Second, the role of the non-native language in translating. Third, the type of language that is deployed in a translation.